Conjuncture of basic sanitation and municipal sanitation plan in Belém do Pará in the eastern amazon (Research, Society and Development, 2020)
Currently, one of the difficulties is the safeguarding of the right to basic sanitation and the maintenance of water resources in the face of the lack of investments, the growth of cities and the inefficiency of public policies that affect the most vulnerable population. Thus, adversities involving plumbing with accumulation of waste and solid waste, dwellings without sanitation and drinking water and their consequences are evident in the city of Belém, in the state of Pará. As a result, the research aimed to analyze the legal regulation on the Plan Municipal Basic Sanitation (PMSB) in the country, as well as data on sanitation in the municipality of Belém and to raise an overview on the topic with emphasis on water supply and sanitation. The methodology focused on the collection and analysis of data from the municipality, consistent with the National Sanitation Information System (SNIS), from 1997 to 2017, data from the Trat Brazil Institute, as well as legislation applied to the matter. The analysis allowed us to conclude that the PMSB elaboration numbers are still insufficient, with emphasis on the North region, where only 22% of the municipalities presented the PMSB. In addition, among the largest Brazilian cities between 2010 and 2017, Belém was among the 10 worst with sanitation coverage, with the exception of 2014. Data corroborated with the information extracted from the SNIS from 1997 to 2017, which indicate the insufficiency of water and sewage and do not keep up with population growth, demonstrating that universalization still faces many challenges to achieve.